FORMULASI DAN EVALUASI KRIM EKSTRAK BAWANG TIWAI (Eleutherine bulbosa) - Husnul Warnida; Henny Nurhasnawati (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Exposure of the skin to ultraviolet (UV) radiation from the sun has various adverse effects, photoaging and skin cancer are of great concern. The ability of botanical antioxidants for prevention of photocarcinogenesis and photoaging had been widely known. Bawang tiwai (Eleutherine bubosa) is traditionally used by the native people of Kalimantan for cancer treatment. The ethanolic extract of bawang tiwai originated from Banjarbaru district, South Kalimantan had strong antioxidant activity. The objective of the study was to formulate Eleutherine bulbosa extract into cream and evaluate its scavenging activity. Antioxidant activity of Eleutherine bulbosa cream was assessed by 2-diphenyl-1-picrylhydrazyl (DPPH) method. The Eleutherine bulbosa extract was incorporated into five cream formulas in varied concentration of emulsifying wax and cetyl alcohol. Evaluation of cream including physical appearance, pH, viscosity, stability, and microbial growth test. The result showed that Eleutherine bulbosa cream has antioxidant activity and good physicochemical quality